8ab-4ac=[latex] x^{4} [/latex] + [latex] x^{3} [/latex] =a*(a+3)-2(a+3)=20[latex] a^{4} [/latex][latex] b^{4} [/latex] - 15[latex] a^{2} [/latex][latex] b^{5} [/latex]

8ab-4ac= [latex] x^{4} [/latex] + [latex] x^{3} [/latex] = a*(a+3)-2(a+3)= 20[latex] a^{4} [/latex][latex] b^{4} [/latex] - 15[latex] a^{2} [/latex][latex] b^{5} [/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex]a)\ 4a(2b-c)\\ b)\ x^3(x+1)\\ c)\ (a+3)(a-2)\\ d)\ 5a^2b^4(4a^2-3b)[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы